Notch Signaling in Myeloid Cells as a Regulator of Tumor Immune Responses - Hossain, Fokhrul; Majumder, Samarpan; Ucar, Deniz A.; Rodriguez, Paulo C.; Golde, Todd E.; Minter, Lisa M.; Osborne, Barbara A.; Miele, Lucio (Frontiers in Immunology, 2018)
Cancer immunotherapy, which stimulates or augments host immune responses to treat malignancies, is the latest development in the rapidly advancing field of cancer immunology. The basic principles of immunotherapies are either to enhance the functions of specific components of the immune system or to neutralize immune-suppressive signals produced by cancer cells or tumor microenvironment cells. When successful, these approaches translate into long-term survival for patients. However, durable responses are only seen in a subset of patients and so far, only in some cancer types. As for other cancer treatments, resistance to immunotherapy can also develop. Numerous research groups are trying to understand why immunotherapy is effective in some patients but not others and to develop strategies to enhance the effectiveness of immunotherapy. The Notch signaling pathway is involved in many aspects of tumor biology, from angiogenesis to cancer stem cell maintenance to tumor immunity. The role of Notch in the development and modulation of the immune response is complex, involving an intricate cross-talk between antigen-presenting cells, T-cell subpopulations, cancer cells and other components of the tumor microenvironment. Elegant studies have shown that Notch is a central mediator of tumor-induced T-cell anergy and that activation of Notch1 in CD8 T-cells enhances cancer immunotherapy. Tumor-infiltrating myeloid cells, including myeloid-derived suppressor cells (MDSC), altered dendritic cells (DC) and tumor-associated macrophages (TAM) along with regulatory T cells (Treg) are major obstacles to the development of successful cancer immunotherapies. In this article, we focus on the roles of Notch signaling in modulating tumor-infiltrating myeloid cells, and discuss implications for therapeutic strategies that modulate Notch signaling to enhance cancer immunotherapy.